An Economic Analysis of Bovine Milk Production in Bhagalpur District of Bihar, India - Ram Kumar Mandal; Sujita Kumari Sharma; Sandeep Kumar; M.K. Wadhwani; Veerabhadrappa Bellundagi; Nitu Kumari; Shalani Kumari; Ramnath Kumar Ray (Business, Management and Economics: Research Progress Vol. 5, 2024)
The annual maintenance costs C of overall farms were estimated to be <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 1.17 lakhs of crossbred cows, <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 86.72 thousand of buffaloes, and <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 36.28 thousand of local cows. The overall cost of production of milk was estimated to be <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 29.17 per Kg of milk of crossbred cows, <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 29.35 per Kg of milk of buffaloes, and 32.64 per Kg of milk of local cows. Gross returns of crossbred cow’s milk of the overall farm were accounted for in 1.52 lakh per year per crossbred cow, <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 1.12 lakh per year per buffalo, and <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 44.85 thousand per year per local cow. The annual cash flow statement of benefit-cost ratio (BCR) was estimated to be on average 1.24 higher for crossbred cows, followed by 1.19 for buffalo, and 1.11 for the local cow. The project was approved as the net present value (NPV) was evaluated at <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 2.94 lakhs of crossbred cow, 1.65 lakhs of buffalo, and <img class="ql-img-inline-formula quicklatex-auto-format lazyloaded" title="Rendered by QuickLaTeX.com" src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" alt=" " width="9" height="14" data-src="https://aneescraftsmanship.com/wp-content/ql-cache/quicklatex.com-a74f4bbfdd222fba3ef224f0ba729b9e_l3.png" /> 54.99 thousand of local cow. The internal rate of return (IRR) was estimated to be 59.68 percent for crossbred cows, 37.89 percent for buffalo, and 12.30 percent for local cows of the cash flow statement as a positive association. As dairy farm sizes increase, both annual maintenance and investment costs tend to decrease, particularly due to lower depreciation costs. Larger farms lead to higher gross and net returns. Crossbred cows, buffaloes, and local cows have different lifespans and death periods, with crossbred cows showing the highest financial returns. Increasing farm size generally reduces costs and increases profitability, with crossbred cows showing the highest returns.